Interaction Between Meloidogyne incognita and Tylenchorhynchus brassicae on Tomato. - KHAN, M. WAJID; HAQ, S. (The Libyan Journal of Agriculture, 2023)
Field soils harbour a number of plant parasitic nematodes with different parasitic ability for a host crop. Tomato is one of the most efficient host for Meloidogyne incognita (Kofoid and White. 1919) Chitwood. 1949 and also efficient for Tylenchorhynchus brassicae Siddiqi, 1961. An observation was made on the interaction of these nematodes, and its effect on population build up using tomato plants. The population dynamics of each species were influenced in almost all combinations by other species sharing the same host plant. The presence of both nematodes together on tomato caused reduction in their rate of multiplication and population build up. In concominant inoculations, when inoculum level of M. incognita was kept constant and those of T. brassicae was varied, the population of M. incognita decreased gradually. There was a gradual increase in the final population of T. brassicae with increase in its initial population. But this final population at each level was much below than the population in single inoculations. Reproduction rate of T. brassicae. however, exhibited a gradual decline with increase in the initial population. When inoculum level of T. brassicae was kept constant and those of \1. incognita was varied, in most of the combinations T. brassicae could not maintain its initial population. The population of M. incognita also decreased and was lower than those obtained in single inoculations. The reproduction rale of .V/. incognita, however, did not show any definite trend.